2013
DOI: 10.1007/s11940-013-0234-9
|View full text |Cite
|
Sign up to set email alerts
|

Autologous Hematopoietic Stem Cell Transplantation as a Treatment Option for Aggressive Multiple Sclerosis

Abstract: OPINION STATEMENT: Despite the development of several injectable or oral treatments for relapsing-remitting multiple sclerosis (RRMS), it remains difficult to treat patients with aggressive disease, and many of these continue to develop severe disability. During the last two decades autologous hematopoietic stem cell transplantation (aHSCT) has been explored with the goal to eliminate an aberrant immune system and then re-install a healthy and tolerant one from hematopoietic precursor cells that had been harve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
1

Year Published

2014
2014
2016
2016

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 32 publications
0
17
0
1
Order By: Relevance
“…43 Different conditioning regimens may diversely affect the immune system. [8][9][10] Mechanistic evaluations on the effects of AHSCT for MS are limited to thymic recovery and regulatory T-cell reconstitution.…”
Section: Discussionmentioning
confidence: 99%
“…43 Different conditioning regimens may diversely affect the immune system. [8][9][10] Mechanistic evaluations on the effects of AHSCT for MS are limited to thymic recovery and regulatory T-cell reconstitution.…”
Section: Discussionmentioning
confidence: 99%
“…High-dose immunosuppressive regimens, followed by autologous hematopoietic stem cell transplantation (AHSCT), have been used with satisfactory results, controlling or reducing disease progression in most patients with refractory disease (7)(8)(9)35,42).…”
Section: Introductionmentioning
confidence: 99%
“…Hematopoietic stem cell transplantation (HSCT) has been reviewed in detail elsewhere [112][113][114][115][116]. Studies on animal models showed that strong immunosuppression followed by syngeneic bone marrow transplantation can induce long term antigen-specific tolerance [117].…”
Section: Autologous Bone Marrow Transplantationmentioning
confidence: 99%